Effectiveness of Group Guidance Using Behavioral Therapy Techniques to Prevent Bullying Problems in Santri - Mey Syandry Khairunnisa; Uli Makmun Hasibuan; Aprillia Malika Putri; Ardella Adawiyah (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2024)
The rise of bullying that occurs in the school environment today is very worrying. One of the impacts is targeting the perpetrator, namely aggressive behavior. This research aims to determine the bullying behavior of students, both seniors and juniors, in Islamic boarding school environments. The main perpetrators in this research were female students and female students who were involved in bullying at Islamic boarding schools. The method used in this research is a qualitative method and literature study. The data collection techniques used in this research were interviews with bullying victims directly and literature studies through journals and books. The results of the discussion from this research are that bullying behavior is rampant in Islamic boarding school environments, both direct and indirect bullying. Bullying not only often occurs due to factors in the Islamic boarding school environment, parents are also very influential in the perpetrators of bullying which often occurs in the Islamic boarding school environment. The impact of bullying is also very bad for the health of the victims, quite a few victims experience depression, excessive fear and worry easily.